Social cohesion among Syrian und Turkish children, adolescents and young adults in Turkey - Nitya Mittal; Marta Parigi; Sebastian Vollmer (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2021)
Turkey has experienced a large influx of Syrian refugees since the start of Syrian civil war. Integration and social cohesion are thus important questions and priorities of public policy in Turkey. We study social cohesion among young Turkish nationals and Syrian refugees. Our study sample comprises of adolescents and young adults (12-30 years), and children (6-11 years) who participated in events of "The Education Program for Syrian Refugees and Host Communities" (BILSY) project conducted by the German Corporation for International Cooperation (GIZ). Social cohesion among adolescents and young adults is measured by means of three dimensions - sense of belonging, trust, and relational capacity. For children, we use behavioural games to measure two dimensions of social cohesion - altruism and trust. Our results show high social cohesion for both age groups, though lack of reciprocal trust from Turkish nationals is an area of concern. We also evaluate the impact of participation in events of the BILSY project with a randomized design and find that it had no impact on social cohesion.
Keywords: 330; Soziale Stabilität; Soziale Integration; Flüchtlinge; Kinder; Jugendliche; Junge Erwachsene; Syrer; Türken; Türkei